E-loyalty formation : a cross-cultural comparison of Spain and Colombia (2018)
This article’s objective is to explore the differences between online shopping behavior in two different markets by explaining the attitudinal and behavioral loyalty of consumers. The proposed model identifies the antecedents of loyalty, as analyzed from different aspects. The model is tested by personal interview surveys of 585 online shoppers in Colombia and Spain. The results indicate that nationality moderates different aspects of the loyalty formation process. In the case of Colombian consumers, affective elements are key determinants of their loyalty attitude, whereas for Spanish online shoppers, attitudinal loyalty is determined primarily by perceived enjoyment in the shopping process, highlighting the importance of hedonic factors in the shopping experience. A significant difference was also found in the satisfaction-attitudinal loyalty relationship between the samples, which tests positively in Colombia but has no significant effect in Spain. Thus, it is proposed that with more experienced consumers, there is greater demand for hedonic elements and less demand for affective elements. The article presents the primary elements for generating attitudinal loyalty among online consumers in an emerging country and finds substantial differences to consumers in a developed country. Suggestions are made for companies that want to adopt an online presence.